Relationship between service quality, memorable tourism experience, satisfaction and loyalty in ecotourism context - Thoo, Poh Yee (2023)
Service quality and satisfaction are critical factors in destination loyalty, as per the expectation-confirmation theory (ECT). However, recent studies have challenged the direct impact of service quality on satisfaction and loyalty behaviour in national park experiences, highlighting the need to re-evaluate causal effects in protected area research. Bako National Park (Bako NP), the oldest and most popular national park in Sarawak, has been criticised for unsatisfactory services and facilities, with visitors leaving negative reviews on popular tourism websites like TripAdvisor and Google. Based on the extant literature review, there is currently a lack of scientific research on visitors' destination loyalty towards Bako NP. Thus, this study aims to address these gaps. First, it seeks to determine the level of service quality, satisfaction, memorable tourism experiences (MTEs), and destination loyalty among the visitors of Bako NP. Subsequently, this study examines the causal relationships between these constructs and explores whether satisfaction and MTEs mediate the relationship between service quality and destination loyalty. A self-administered online survey was carried out and generated 123 samples. Data was analysed by descriptive analysis and partial least squares structural equation modelling (PLS-SEM). The results indicated that the level of service quality and MTEs were high, as were satisfaction and destination loyalty. PLS-SEM analysis outcomes demonstrated all causal relationships between the constructs except for the direct relationship between service quality and destination loyalty. The analysis also revealed that satisfaction and MTE significantly mediated the relationship between service quality and destination loyalty. However, these findings contradicted the negative online reviews, necessitating a focused group discussion (FGD) with the Bako NP management to provide a better understanding of the underlying reasons behind this. The FGD outcomes revealed that Bako NP management prioritises service quality and has taken proactive measures to upgrade its facilities and accommodations in recent years, addressing any broken amenities promptly, and suggesting most visitors did return to Bako NP due to their memorable experiences from previous visits. The management also highlighted that focusing on visitor experiences has emerged as a crucial factor in the success of Bako NP, more than other factors. Hence, this study confirms previous research on the significance of prioritising visitor satisfaction and MTE, as demonstrated by the clear relationship between service quality, satisfaction, MTE, and destination loyalty. These findings offer valuable theoretical and practical contributions. For Bako NP management, incorporating these insights into their strategic planning presents a clear opportunity to improve visitor experiences and foster loyalty. However, it must be highlighted that the lack of generalisability is the primary limitation of this study since the survey employed convenience sampling and relied on an online platform during the COVID-19 pandemic-induced lockdown period. Therefore, it is recommended that future research should replicate this model for multi-group or crosscultural studies in Bako NP or other national park destinations. By validating these findings, the breadth of knowledge in this field can expand and enrich our understanding of visitor experiences in national parks.